Identify the preferred and perceived coaching styles in collegiate football teams - Trajano, Marianne Monica Krnkva 2002-
Athlete’s preferences with regards to coaching styles include coaches helping them progress with their skill and decision-making, as well as build a positive relationship to build a quality impact on the team (Coykendall, 2014). There are various ways in which coaches mentor their athletes. Depending on the individual and the circumstance at hand, these may affect the athletes on different factors. This study identified the coaching style preference and perception of collegiate male and female football athletes of their coach’s coaching style. To answer this question, the researcher used the Leadership Scale for Sports and had respondents complete it. Respondents were chosen from a university using the convenience purposive method to gather female and male football student- athletes. Data gathered using the questionnaire will then be analyzed using Pearson's Correlation Coefficient to determine the degree of association between the two variables. After conducting the Pearson’s correlation coefficient, the subscale Training and Instruction has a moderate correlation for both teams with (r = 0.59, p-value .02) for male athletes, and (r = 0.53, p-value = .04) for female athletes for preferred and perceived versions. The results showed that there were two (2) preferred behaviors of both teams; namely Training and Instruction and Positive Feedback. Athlete’s perception of their coach also showed Training and Instruction behavior from both teams. Positivity will come out when the athlete’s perception and preference of the coach's coaching styles are aligned (May et.al, 2014)